Pengaruh Analisis Kebutuhan Pelatihan Budaya Keamanan Siber Sebagai Upaya Pengembangan Kompetensi bagi Aparatur Sipil Negara di Era Digital - Sri Cahaya Khoironi (Jurnal Studi Komunikasi dan Media, 2020)
The results of Monitoring and Evaluation of Electronic-Based Government Systems (SPBE) that not been optimal, the high incidence of cyber in the government domain. go.id due to system vulnerability as well as the number of government pages with unsafe conditions and not in accordance with existing international standards, show the need for ASN as a manager of digital competence to oversee digitalization in the government environment. To discuss this issue, the method chosen was the study of literature, by reviewing various literature and collection of research results in accordance with the problem. Descriptive qualitative analysis using the technique "PRISMA protocol". The findings of this study are important for designing training programs as part of the development of sustainable digital ASN competencies, specifically related to training in cybersecurity culture in government environments, especially in public services. Given the technology and knowledge of hacking efforts in cybercrime is developing very fast, it is necessary to anticipate investment in human resources through training in cybersecurity cultureHasil Pemantauan dan Evaluasi Sistem Pemerintahan Berbasis Elektronik (SPBE) yang belum optimal dan tingginya insiden siber pada domain pemerintah.go.id akibat dari kerentanan sistem serta masih banyaknya laman pemerintah dengan kondisi tidak aman dan belum sesuai standar internasional yang ada menyiratkan adanya kebutuhan ASN sebagai pengelola yang berkompetensi digital untuk mengawal digitalisasi di lingkungan pemerintahan. Metode yang dipilih adalah studi kepustakaan dengan meninjau berbagai literatur dan kumpulan hasil-hasil penelitian sesuai dengan permasalahan. Analisis deskriptif kualitatif menggunakan teknik “PRISMA protokol”. Temuan dari penelitian ini penting untuk merancang program pelatihan sebagai bagian dari pengembangan kompetensi digital ASN yang berkelanjutan, khususnya terkait pelatihan budaya keamanan siber di lingkungan pemerintahan, terutama dalam pelayanan publiknya. Mengingat teknologi dan pengetahuan tentang upaya peretasan dalam kejahatan siber berkembang sangat cepat, perlu antisipasi investasi sumber daya manusia melalui pelatihan budaya keamanan siber.